2003
DOI: 10.1021/ja021003+
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase SN2 and Bromine Abstraction Reactions of Chloride Ion with Bromomethane:  Reaction Cross Sections and Energy Disposal into Products

Abstract: Reaction cross sections and product velocity distributions are presented for the bimolecular gas-phase nucleophilic substitution (S(N)2) reaction Cl(-) + CH(3)Br --> CH(3)Cl + Br(-) as a function of collision energy, 0.06-24 eV. The exothermic S(N)2 reaction is inefficient compared with phase space theory (PST) and ion-dipole capture models. At the lowest energies, the S(N)2 reaction exhibits the largest cross sections and symmetrical forward/backward scattering of the CH(3)Cl + Br(-) products. The velocity di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 87 publications
5
90
0
1
Order By: Relevance
“…They found, as in ref. [39], other reaction channels which, however, are not of concern for the present Review.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…They found, as in ref. [39], other reaction channels which, however, are not of concern for the present Review.…”
mentioning
confidence: 87%
“…Graul and Bowers [33] found that the translational energy distribution of the products (Br À and CH 3 Cl) is smaller than the phase space theory (PST) prediction, which indicates that the product molecule is vibrationally hot. Recently, Angel and Ervin [39] have measured reaction crosssections and product distributions for the reaction Cl À + CH 3 Br for translational energies between 0.06 and 24 eV. At the lowest energies, the S N 2 reaction exhibits the largest cross-sections, and a symmetrical forward/backward scattering of the CH 3 Cl + Br À products is observed.…”
mentioning
confidence: 99%
“…S N 2 reaction. 25 Although not of thermochemical or combustion chemistry interest, this exothermic reaction has a classic double-well potential and the kinetic energy release had previously been studied by metastable ion dissociation, 26,27 providing an interesting test system for comparison with literature results. [26][27][28][29][30][31][32][33][34] At the lowest energies (near room temperature), the product velocity distributions are statistical as modeled by classical phase space theory (which disagrees with the metastable ion dissociation work but might be explained by the different experimental conditions).…”
Section: Product Velocity Distributionsmentioning
confidence: 99%
“…At still higher kinetic energies, a new rebound mechanism is indicated by backward scattering. 25 We further applied product velocity distribution measurements to reaction (10) with RH = CH 4 and C 2 H 6 . 23 These experiments showed definitively that the reactions are non-statistical.…”
Section: Product Velocity Distributionsmentioning
confidence: 99%
See 1 more Smart Citation